The effects of resistance training on myostatin and follistatin in adults: A systematic review and meta-analysis - Khalafi, M.; Aria, B.; Symonds, M. E.; Rosenkranz, S. K. (Physiology & Behavior, 2023)
Introduction and aim Myostatin and follistatin are the main hormones for regulating muscle mass, and previous research suggests they are modulated by resistance training. We therefore performed a systematic review and meta-analysis to investigate the impact of resistance training on circulating myostatin and follistatin in adults.